INDEKS KESENJANGAN: SEBUAH JALAN UNTUK PENINGKATAN KAPASITAS ADAPTASI SEKTOR AIR MINUM TERKAIT PERUBAHAN IKLIM - Heston, Yudha Pracastino (Jurnal Sosial Ekonomi Pekerjaan Umum, 2015)
Climate change can affect the quality and quantity of water resources. Communities in settlements both in metropolitan and rural areas need to take adaptation action from planning, operation, development and evaluation. Integration of adaptation strategies needed to ensure public resources wisely invested. Research has done to find the measures of contextual adaptation capacity gap areas, which need to be improved. Community adaptation theory approach is used to identify the factors related to housing conditions in adapting to climate change. The research method is comparing the indicators ideal and reality in the study area.Object of the study group was divided into two levels, namely the individual and institution. Research sites in two locations: Kupang and Palembang in Indonesia. From discussion there are 3 (three) indicator that have high gap and 3 (three) in medium gap both in Palembang and Kupang. Both Palembang and Kupang have to face, problem in water management at territorial or community level. Palembang should pay attention to local wisdom development, community involvement, netwwork, organization availability, and program benefit development. Kupang should pay attention to job opportunity, effort to increased knowledge, information availibility, channel development, and program agreement.